Scaling of embryonic patterning based on phase-gradient encoding - Lauschke, Volker Martin; Tsiairis, Charisios D.; François, Paul; Aulehla, Alexander (Nature, 2013)
An ex vivo primary culture assay is developed that recapitulates mouse embryonic mesodermal patterning and segment formation; using this approach, it is shown that oscillating gene activity is central to maintain stable proportions during development.
Published online 19 December 2012
Gesehen am 14.10.2021